Exploring Paradigms in Intraoperative Assessment of Resection Margins (IOARM) in Oral Cancer: A Comprehensive Review - Mukul , Sailesh Kumar; Rashid, Sibgutulah; Gupta, Vyakhya Akhileshkumar; Haidry, Naqoosh (Journal of Orofacial Research, 2025)
Oral squamous cell carcinoma (OSCC) presents significant challenges in surgical management, particularly in achieving clear resection margins, which are crucial for reducing recurrence and improving patient outcomes. Traditional methods like visual inspection and palpation are often insufficient for accurate margin assessment. This review delves into advanced intraoperative imaging and assessment techniques, including intraoral ultrasound (ioUS), magnetic resonance imaging (MRI), fluorescence imaging, Raman spectroscopy, and confocal laser endomicroscopy (CLE). It aims to discuss the principles, applications, advantages, limitations, and clinical efficacy in enhancing surgical precision in OSCC treatment.